The quality of spiritual life among students of the College of Education for Girls - Ealoos, آمنة حيدر (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The current study aims to explore the level of spiritual quality of life among female students in colleges of education. Additionally, it investigates statistically significant differences in spiritual quality of life based on the specialization (scientific vs. humanities). To achieve the research objectives, the researcher developed a scale for spiritual quality of life, consisting of 35 items. Psychometric properties were extracted for both individual items and the overall scale. The research tool was applied to the primary sample, which included 200 female students from colleges of education (morning studies) during the academic year 2023-2024. The sample covered both scientific and humanities specializations, across all study levels. Participants were randomly selected. After collecting and statistically analyzing the data using SPSS, the study found the following results: Female students in colleges of education have an average level of spiritual quality of life. Statistically significant differences exist in spiritual quality of life among female students based on their specialization (scientific vs. humanities). In light of these findings, the researcher provided several recommendations and suggestions.